Temperature treatments boost subclinical infections of Batrachochytrium dendrobatidis in a Mexican salamander (Pseudoeurycea leprosa) - Cinthya Mendoza-Almeralla; Aldo López-Velázquez; Ana V. Longo; Gabriela Parra-Olea (Revista Mexicana de Biodiversidad)
The first record about the pathogenic fungus Batrachochytrium dendrobatidis in Mexican plethodontid salamanders dates back to the 1970s. However, little is known of the patterns of infection in wild populations and the effects of changes in temperature on the degree of infection. This work quantified Bd infection in a population of Pseudoeurycea leprosa in La Malinche National Park, Puebla, Mexico from June 2011 to September 2012. A total of 160 adult salamanders were experimentally exposed to temperatures of 10, 15, 20, 23, 25, or 28◦C for 10 weeks. The results of this study revealed that: (1) the population of P. leprosa in La Malinche National Park is infected with Bd throughout the year at a low prevalenceof between 0 and 17%; (2) 20.6% of the salamanders that were Bd negative at the time of collection expressed chytridiomycosis after exposure to the experimental temperature treatments; (3) temperature was the cause of death in each treatment, with temperatures of 25 °C and 28 °C affecting the survival of P. leprosa; (4) the infection load in certain P. leprosa individuals exhibited cycles of increasing and decreasing zoospore genomic equivalents over time.